Long‐term functional results after excisional haemorrhoidectomy. (22nd January 2020) - Lehmann, J.‐P.; Johansson, H. Ö.; Graf, W.
Abstract: Aim: The aim of this work was to perform a long‐term evaluation of a randomized trial focusing on functional aspects after excisional haemorrhoidectomy with a minimum follow‐up of 9 years. Method: A questionnaire‐based study including patients operated on for haemorrhoids in Sweden between 1999 and 2003. A total of 225 patients were randomized to Milligan's or Ferguson's operation. Twenty‐six patients had died and 151 (76%) participated after a median follow‐up of 10.7 years (range 9.2–12.6 years). Results: Seventy‐seven patients were in the Milligan group and 74 in the Ferguson group. Forty‐eight (32%) reported recurrence. Anal bleeding was reported in 80% at baseline but in 28% at long‐term follow‐up ( P < 0.0001). At baseline, 49% had spontaneous anal pain and 25% pain at defaecation. At follow‐up, these figures were 17% and 11%. At follow‐up, 19% described a sense of anal stenosis. At baseline, soiling was reported in 51% but in 20% at long‐term follow‐up ( P < 0.001). Nineteen per cent used pads preoperatively and 6% at follow‐up ( P < 0.0001). Straining at defaecation was reported by 35% at baseline. At follow‐up, this figure was 25% ( P = 0.055). Conclusion: Symptoms associated with haemorrhoids were reduced at long‐term follow‐up. The most common problems were perceived recurrence and a sense of anal stenosis.